The Relationship of Physical Properties of Rock to The Slope Stability of The Progo River Cliff in Sentolo-Sedayu, Kulon Progo, Yogyakarta, Indonesia - R.A.T. Listyani; Dianto Isnawan; R.Andy Erwin Wijaya (International Journal of Hydrological and Environmental for Sustainability, 2023)
To support the increasingly advanced development of the Kulon Progo area, road access via the Progo River bridge needs to be maintained in instability. To support this, an engineering geological survey was carried out to find out the relationship between the physical properties of rocks and the stability of slopes on the cliffs of the Progo River. The research method begins with a field survey to obtain lithology and slope geometry data. Scanlines at selected locations were carried out to determine discontinuity areas and interpret rock weathering using a Schmidt hammer. Physical laboratory tests are useful for determining the bulk density and porosity of rocks, while from rock mechanical tests (shear strength) cohesion and friction angle values are obtained. The results of the safety factor analysis using the Slide program show that the slopes generally have a medium-high level of severity (Fk < 1.2), supported by quite a lot of joint areas, varying porosity (4.12 – 25.10%) and the level of weathering is at level III-IV. Rock porosity is less related to slope strength, while weathering generally reduces slope stability.